Orocaecal Transit Time in Chronic Diarrhea - Marcellus Simadibrata; Paulus Simadibrata; Badriul Hegar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Background: The diagnosis and treatment of chronic diarrhea is sometimes difficult. Orocaecal transit time may explained some pathogenesis mechanism in chronic diarrhea. Methods: Twenty six chronic diarrhea patients and 35 normal adult subjects were included in this study. After fasting for at least 10 hours, subjects were asked to drink 20 ml (13.3 g) lactulose, then performed the breath hydrogen test. If there were an increment of H2 concentration 10 ppm in ½ -1 hour, the subject was considered as rapid transit time. If an increment of H concentration 10 ppm in 1 - 2 hour, the subject was considered as normal transit time. If an increment of H2 concentration 10 ppm in 2 - 3 hour,the subject was considered as delayed transit timeResults: In the chronic diarrhea group, 10 (38.4%) had rapid OCTT, 15 (57.6%) had normal OCTT and only 1 (4%) had delayed OCTT. In the normal adults group, 2 (5.7%) had rapid OCTT, 22 (62.9%) had normal OCTT and 11 (31.4%) had delayed OCTT. The difference was statistically significant (p 0.001). The mean value of OCTT in chronic diarrhea and normal adults were 84.23 + 39.82 min vs. 114.00 + 51.35 min (p = 0.027). Conclusions: The rapid OCTT was more likely to be found in the chronic diarrhea patients compare to normal adults significantly. The mean OCTT in chronic diarrhea was shorter than the mean OCTT in normal adults.   Keywords: orocaecal transit time, OCTT, chronic diarrhea